2007
DOI: 10.1097/01.pai.0000201808.35931.78
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Expression in Non–small-cell Lung Carcinomas: Correlation With Apoptosis and Other Apoptosis-related Proteins, Clinicopathologic Prognostic Factors and Prognosis

Abstract: The role of survivin that regulates the biological behavior of non-small-cell lung carcinoma (NSCLC) is still controversial. We aimed to investigate survivin expression in NSCLC and to define any correlation with expressions of p53, bcl-2, bax, apoptotic index (AI), tumor cell proliferation, clinicopathologic variables, and overall survival. Tumors of 63 patients with NSCLC were examined for expressions of survivin, p53, bcl-2, bax, and Ki-67 by immunohistochemistry. AI was also evaluated. Results for each ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Third, it may be due to the variable criteria used to classify a tumor as having more nuclear survivin or cytoplasmic survivin. 24,29,46 As the balance between cytoplasmic and nuclear survivin in tumor cells may be considered as an indicator for 'active survivin,' it is advisable to quantify not only absolute expression levels, but also the relative intracellular localization of survivin, cytoplasmic, nuclear, total (cytoplasmic þ nuclear), and the difference in survivin expression (cytoplasmic -nuclear). 45 Our results showed that cytoplasmic survivin (log rank test, adenocarcinoma, Po0.001; squamous cell carcinoma, P ¼ 0.005) and the difference in survivin (log rank test, adenocarcinoma, Po0.001; squamous cell carcinoma, P ¼ 0.014) was associated with a poorer survival rate, whereas nuclear survivin expression (log rank test, adenocarcinoma, P ¼ 0.006; squamous cell carcinoma, P ¼ 0.050) was associated with a favorable survival rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, it may be due to the variable criteria used to classify a tumor as having more nuclear survivin or cytoplasmic survivin. 24,29,46 As the balance between cytoplasmic and nuclear survivin in tumor cells may be considered as an indicator for 'active survivin,' it is advisable to quantify not only absolute expression levels, but also the relative intracellular localization of survivin, cytoplasmic, nuclear, total (cytoplasmic þ nuclear), and the difference in survivin expression (cytoplasmic -nuclear). 45 Our results showed that cytoplasmic survivin (log rank test, adenocarcinoma, Po0.001; squamous cell carcinoma, P ¼ 0.005) and the difference in survivin (log rank test, adenocarcinoma, Po0.001; squamous cell carcinoma, P ¼ 0.014) was associated with a poorer survival rate, whereas nuclear survivin expression (log rank test, adenocarcinoma, P ¼ 0.006; squamous cell carcinoma, P ¼ 0.050) was associated with a favorable survival rate.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of nuclear versus cytoplasmic expression of survivin with apoptosis and the expression of HuR-related COX-2 expression is not well characterized in primary human lung cancers. [23][24][25][26][27][28][29][30][31] In this study, we evaluated the expression of survivin, COX-2, and HuR, and subcellular localization of survivin and HuR in sets of pulmonary adenocarcinomas and squamous cell carcinomas patients, in relation to clinicopathologic parameters and survival. In addition, we investigated the relation of survivin, COX-2, and HuR expression.…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9] Recent studies have also shown that survivin expression levels correlate with oncogenesis, aggressiveness of tumors and poor clinical outcome in NSCLC. [10][11][12][13][14][15] To target survivin overexpression as a cause of lung cancer, strategies have been designed to inhibit survivin synthesis with the hope of preventing or mitigating NSCLC. [16][17] DNA methylation is a critical epigenetic modification that silences gene transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that increased survivin expression was associated with various cancers including bladder, colorectal, lung and oral [6][7][8][9][10]. A previous study reported that survivin was detected in urine samples from patients with new or recurrent bladder cancer but not found from healthy volunteers [11].…”
Section: Introductionmentioning
confidence: 99%